The Effectiveness of Bariatric Surgery for Chinese Obesity in 2 Years: A Meta-Analysis and Systematic Review. (3rd September 2017) - Zeng, Tianshu; Cai, Yuli; Chen, Lulu
ABSTRACT: Aim : Bariatric surgery is becoming an acceptable option for treatment of obesity worldwide, but there is no systemic review and meta-analysis focusing on obese patients in China. This study is to quantify the overall effects of bariatric surgery for Chinese obesity using up-to-date, comprehensive data. Methods : We systematically searched MEDLINE, EMBASE, Cochrane Library, ISI Web of Science, and CNKI databases in English and Chinese. The weighted mean difference (MD) and 95% confidence interval (CI) were calculated from the original literature. Obese Chinese adults (body mass index [BMI] ≥ 30 kg/m 2 ) with a minimum six-month follow-up were included. Results : The meta-analysis included 23 literature reviews with 1, 316 morbidly Chinese obese adults. Bariatric surgery could significantly decrease the levels of BMI (MD = 10.75 kg/m 2, 95% CI: 8.65–12.85, p <.01) and hemoglobin A1c (MD = 2.15%, 95% CI: 1.55–2.75, p <.00001), and improve lipid profile dramatically. In the subgroup analysis by BMI values, subjects lost more weight in BMI ≥ 40 kg/m 2 group (MD = 14.01 kg/m 2, 95% CI: 11.20–16.82) than BMI < 40 kg/m 2 group (MD = 8.09 kg/m 2, 95% CI: 6.49–9.68, p <.00001) after surgery. When we stratified analysis by surgical procedures, fasting blood glucose decreased more in gastric bypass group (MD = 3.08 mmol/L, 95% CI: 2.18–3.98) than restrictive procedures (MD = 1.27 mmol/L, 95% CI: 0.45–2.09, p =.008) and postprandial blood glucose levels (gastric bypass procedures: 8.44 mmol/L, 95% CI: 6.83–10.04; restrictive procedures: MD = 2.80 mmol/L, 95% CI: 1.86–3.74, p <.00001). Conclusions : Bariatric surgery provides substantial metabolic effects for Chinese morbid obese adults at least in a relative short term. Further high-quality randomized controlled trials with long follow-up periods are needed to provide more reliable evidence.